2022
DOI: 10.3390/ijerph19148783
|View full text |Cite
|
Sign up to set email alerts
|

Assisting Strategies of the Parents of Students with Special Educational Needs in the Emergency Remote Learning in Poland

Abstract: The study had four objectives: (a) identifying and characterizing strategies for involving parents of students with SEN (students with special educational needs) in remote education during the COVID-19 pandemic; (b) comparing these strategies with those used by parents of students without SEN (non-SEN students); (c) identifying predictors of parental involvement in the remote education of students with SEN; (d) checking whether the identified strategies differentiate the perceived barriers and benefits of remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
(35 reference statements)
0
0
1
Order By: Relevance
“…Our findings related to the perceptions of stability of support for pupils' learning during the pandemic were in contrast with research in various educational contexts that reported on the reduction of IEP service provision during the COVID-19 pandemic (e.g., Castro-Kemp & Mahmud, 2021;Chen et al, 2022;Colombo & Santagati, 2022;Toseeb et al, 2020) and about a simultaneous increase in parental involvement in children's education (e.g., Couper-Kenney & Riddell, 2021;Knopik et al, 2022;Nusser, 2021). Several factors might be responsible for the observed differences in these findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings related to the perceptions of stability of support for pupils' learning during the pandemic were in contrast with research in various educational contexts that reported on the reduction of IEP service provision during the COVID-19 pandemic (e.g., Castro-Kemp & Mahmud, 2021;Chen et al, 2022;Colombo & Santagati, 2022;Toseeb et al, 2020) and about a simultaneous increase in parental involvement in children's education (e.g., Couper-Kenney & Riddell, 2021;Knopik et al, 2022;Nusser, 2021). Several factors might be responsible for the observed differences in these findings.…”
Section: Discussioncontrasting
confidence: 99%
“…The latter, in particular, has been proven to be one of the biggest problems for all parents and is emphasised even more by parents of children with ASN (Nusser, 2021). In addition, Knopik et al (2022) found that parents of children with ASN were likelier to extensively support and motivate their children in learning than other parents. As Couper-Kenney and Riddell (2021) noted, many parents of children with ASN described the extra work required on behalf of their children, from requesting work and providing one-on-one support to creating structures at home that are appropriate for each child.…”
Section: Parental Involvement In the Education Of Children With Asn D...mentioning
confidence: 99%
“…Even though parents of children with ASN are often more actively and intensely involved in their children's education, viewing their involvement as highly essential to their children's positive learning outcomes (Hornby & Lafaele, 2011), their involvement became even more intensified during the pandemic. Indeed, research shows that the level of parental investment in the education of students with ASN was higher than that of the general student population during the pandemic (Knopik et al, 2022;Nusser, 2021). For example, German parents of eighth graders with ASN have reported spending twice as many hours (approximately 11 hours) helping their children learn compared with parents of children without ASN (Nusser, 2021).…”
Section: Parental Involvement In the Education Of Children With Asn D...mentioning
confidence: 99%
See 1 more Smart Citation